2020
DOI: 10.1002/jcla.23539
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitation of four androgens and 17‐hydroxyprogesterone in polycystic ovarian syndrome patients by LC‐MS/MS

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…The method in the present study requires an additional derivatization step compared to the direct measurement. However, compared to these reports, the LLOQ of DHT (14.5 pg/mL) in the present study showed higher sensitivity than hydroxylamine hydrochloride derivatization [18] or direct measurement [19,23] by using LLE after PA derivatization. Also, methods using solid-phase extraction have been developed for the detection of steroids, but these methods are not efficient in time and cost -effective compared with liquid-liquid extraction [16,24,25].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The method in the present study requires an additional derivatization step compared to the direct measurement. However, compared to these reports, the LLOQ of DHT (14.5 pg/mL) in the present study showed higher sensitivity than hydroxylamine hydrochloride derivatization [18] or direct measurement [19,23] by using LLE after PA derivatization. Also, methods using solid-phase extraction have been developed for the detection of steroids, but these methods are not efficient in time and cost -effective compared with liquid-liquid extraction [16,24,25].…”
Section: Discussioncontrasting
confidence: 89%
“…Similar to the acylation reaction of fluorinated anhydrides and the hydroxyl group of the seventeenth carbon position in the steroid reaction, derivatization using PA showed a higher sensitivity in the detection of 17-OH steroids, such as corticosteroids, in ESI-LC/MS [ 17 ]. Recently, LC-MS based quantification methods for androgens such as DHT that utilize various sample sources were developed, and 5AR inhibition studies were conducted [ 16 , 18 , 19 , 20 , 21 , 22 ]. The method in the present study requires an additional derivatization step compared to the direct measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The LLOQs was calculated by analysing the serially diluted QC specimens spiked with IS over 5 days. The LLOQ was defined as the average concentration at which the S/N ratio >10, CV <20% and bias were within ±20% [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The precision was evaluated by intra-assay precision ( n = 10 batches) and inter-assay precision ( n = 25 batches from three separate days) estimation with QC materials. The accuracy was assessed by the recovery studies, in which the recovery of each androgen was calculated at high-, medium-, and low-level QCs by comparing the IS peak area ratio of extracted QC samples to the IS peak area ratio of non-extracted standard solutions at the same concentration [ 19 ]. The stability of the analytes in plasma was assessed by evaluating plasma samples kept at 4 and 21 °C (room temperature) for 6 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation